Analisis Kompetensi Sosial Guru Membentuk Karakter Siswa di SMP Negeri 35 Medan - Eunike Br Simanjuntak; Relly Tamba; Sri Yunita; Stevan Oktureja Pasaribu (Departement of Mathematics Education, 2023)
Teacher competence is one of the factors that influence the achievement of learning goals and school education. Teachers must have skills that can be used in the classroom, including teacher social skills. The purpose of this study was to describe the social competence of class VIII SMP teachers. This type of research is descriptive qualitative research. The results showed that the competence of grade VIII junior high school teachers was in the